A systematic review of security challenges in vehicular platooning - CARNEIRO, Igor Fernandes (2023)
The industry and academia have been paying much attention to autonomous vehicles (AV) since this technology promises to increase mainly road safety and fuel efficiency. Vehicle platooning is a sub-field of AVs that aims to group vehicles on the road to achieve those benefits. Usually, the formation is a leader vehicle that guides the follower vehicles to the destination. This work systematically reviews relevant articles from the literature about security in vehicle platooning. The goals are to point out the main security issues and current solutions, identify research tendencies and give future research directions for security in vehicle platooning. The analysis showed that network and application-layer issues are the only topics in vehicle platooning articles. In contrast, the autonomous vehicles (AV) field also includes system issues. The issues in the platoon realm are related to string stability, and the solutions try to prevent them from getting broken. Moreover, although the general field (AV) and the sub-field (platoon) don't share many vulnerabilities, malware attacks were identified as potential threats to platoons. Despite these findings, the chosen parameters for this systematic review limited the achievement of more accurate results about the research tendencies and gaps in the platoon field. Using the same methodology, future systematic reviews on this theme shall improve the search term and increase the number of reviewed articles.